NEED ANALYSIS FOR ENGLISH FOR SPECIAL PURPOSES (ESP) IN INFORMATICS MANAGEMENT CLASS AT ABC UNIVERSITY. - Heri Kurniawan, Andreas; Nining Fitriani (Jurnal Pendidikan dan Sastra Inggris, 2022)
The process of learning English with ESP (English for Specific Purposes) in higher education often runs less than optimally. One of the contributing factors is the lack of lesson planning so that learning takes place irrelevant to the field of knowledge they teach. For this reason, it is necessary to have a learning plan which will begin by analyzing student needs for learning English with special objectives. Therefore, the research aims to find and describe students' needs for ESP English. This needs to be done so that the English language learning materials with special purposes (ESP) received by students are in accordance with the field of knowledge they are capable of and the field of work they will be engaged in. This research is based on a qualitative descriptive approach. The object of this research is Informatics Management students class of 2020/2021 University of Computer Science and Technology. Data collection techniques used were questionnaires and direct interviews. Then the data obtained will be classified so that the needs of Informatics Management students for learning English can be identified, then they will be described. The results of this study will be used as a reference for subsequent research, namely syllabus planning and development of teaching materials for ESP English. Keywords: need analysis, ESP, English teaching.